Implantation of sigmoid colon cancer into the endoscopic resection site of intramucosal rectal cancer: A case report - Kyohei Nishino; Masanori Hongo; Naoko Mori; Kazumi Shimamoto; Yu Kobayashi; Fumiyasu Nakamura; Michiko Hino; Takeshi Togawa; Akira Andoh; Hiromitsu Ban (DEN Open, 2023)
Abstract A 70‐year‐old woman was diagnosed with intramucosal rectal cancer and advanced sigmoid colon cancer at the same time. First, the intramucosal rectal cancer was curatively resected by endoscopic submucosal dissection, and surgery was subsequently performed for sigmoid colon cancer. After 20 months, a follow‐up colonoscopy revealed a tumor growth at the ulcer scar of the endoscopic submucosal dissection. Histological findings and KRAS mutation analysis suggested implantation of sigmoid colon cancer to the post‐endoscopic submucosal dissection site of intramucosal rectal cancer.